New ecological realisms : post-apocalyptic fiction and contemporary theory - Kaup, Monika (Speculative realism., 2021)
"What is the singular reality of humanistic objects of study? By pairing post-apocalyptic novels by Margaret Atwood, José Saramago, Octavia Butler and Cormac McCarthy with new realist theories, Monika Kaup shows that, just as new realist theory can illuminate post-apocalyptic literature, post-apocalyptic literature also embeds new theories of the real."--